Aqueous electrochemistry: The toolbox for life's emergence from redox disequilibria. Issue 2 (11th March 2022) - Nitschke, Wolfgang; Schoepp‐Cothenet, Barbara; Duval, Simon; Zuchan, Kilian; Farr, Orion; Baymann, Frauke; Panico, Francesco; Minguzzi, Alessandro; Branscomb, Elbert; Russell, Michael J.
Abstract: The second law of thermodynamics leaves no doubt that life on planet Earth and its inherent substantial decrease in entropy is fundamentally based on mechanisms converting environmental free energy into the spatial and temporal order of metabolic processes. This argument holds for present life as much as it does for its very beginnings some 4 billion years ago. In this contribution, we try to strip down free energy conversion in extant life (known as "bioenergetics" to the biologists) to its basic principles with the aim to potentially retrodict the nature of the pre‐biotic precursor which drove life into existence. We demonstrate that these basic principles are deeply rooted in aqueous electrochemistry and strongly rely on inorganic redox compounds. The question of life's emergence, generally considered to fall into the realm of organic chemistry, should therefore rather be recognized as an electrochemical problem and its ultimate elucidation will need to strongly implicate the community of electrochemical scientists.